2007
DOI: 10.1007/s00508-007-0819-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in patients with COPD and pulmonary hypertension

Abstract: The study demonstrates the presence of oxidative/antioxidative imbalance in the systemic circulation in patients with COPD: compared with healthy subjects, COPD patients had higher serum MDA concentrations and lower GPX activity in erythrocytes. The magnitudes of the increase in MDA and reduction in GPX activity were similar in COPD patients with pulmonary hypertension and in those with normal pulmonary artery pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 31 publications
(69 reference statements)
3
37
1
1
Order By: Relevance
“…interestingly, Joppa et al in their study described the potential relationship between pulmonary hypertension and markers of systemic oxidative stress in well defined patients with coPD (12). We also found relationship between Pon1 192 gene polymorphisms and low serum Pon1 levels in coPD patients in comparison to healthy non-smokers and smokers withouth coPD.…”
Section: Resultssupporting
confidence: 73%
“…interestingly, Joppa et al in their study described the potential relationship between pulmonary hypertension and markers of systemic oxidative stress in well defined patients with coPD (12). We also found relationship between Pon1 192 gene polymorphisms and low serum Pon1 levels in coPD patients in comparison to healthy non-smokers and smokers withouth coPD.…”
Section: Resultssupporting
confidence: 73%
“…Whereas, erythrocyte GPx activity and TAS showed a significant decrease in the mean value of COPD patients with type 2 diabetes. Joppa et al also reported a significant decrease in the GPx activity in erythrocyte of COPD patients with and without pulmonary hypertension [55]. Some of the previous finding of Orhan et al showed a significant increase in plasma GPx activity in hypertensive preeclamptic pregnancy and also in insulin dependent diabetic pregnancy [56].…”
Section: Discussionmentioning
confidence: 91%
“…PH is the main cause of right ventricular hypertrophy. The pathogenesis of PH is not fully understood: it can be idiopathic and also can share the same pathophysiology and be complicated with other diseases such as chronic obstructive pulmonary disease [10]. The quality of life in patients with PH can be very poor.…”
Section: Introductionmentioning
confidence: 99%